Subchronic Toxicity of the Physalis minima Leaves - Setyawati Soeharto; Dian Nugrahenny; Nur Permatasari; Elly Mayangsari (Research Journal of Life Science, 2018)
The study was to evaluate the subchronic toxicity of aqueous extract of Physalis minima leaves in female rats. Eighteen female Wistar rats were orally administered with aqueous extract of P. minima leaves at doses of 90, 270 and 450 mg/kg BW, respectively for 90 days. Six female rats without any treatment were provided as a control group. At the end of the experiment, blood samples were collected for hematological and biochemical (aspartate transaminase/AST, alanine transaminase/ALT, creatinine, urea, glucose, cholesterol, and triglyceride) analyses. The results showed that hematological and biochemical biomarkers were not significantly different in treated groups compared to the control group. It is concluded that the aqueous extract of P. minima leaves do not induce hematologic toxicity, hepatotoxicity and renal toxicity in the subchronic toxicity study.